The Use of Gamification in Teaching and Learning during Covid-19 Pandemic - Mertika Mertika; Slamat Fitriyadi; Dewi Mariana; Evinna Cinda Hendriana; Wanda Giovani; Rien Anitra; Citra Utami; Rini Setyowati; Heru Susanto (STKIP Singkawang, 2022)
This service activity aims to increase the understanding and knowledge of lecturers about the use of gamification in learning during the Covid-19 pandemic. In addition, this program also provides socialization of what game models can be used to support e-learning lectures on campus, for example using learning applications such as Quiziz and Kahoot or by implementing game learning models such as role playing, NGT and others. The specific target to be achieved is to increase the creativity of lecturers in designing and using gamification in learning during the Covid-19 pandemic so that online learning becomes more fun. The method used in the implementation of this service is in the form of counseling methods, and question and answer.